2010
DOI: 10.1111/j.1469-0691.2010.03210.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of methicillin-resistant Staphylococcus aureus using PCR and chromogenic agar: a prospective study to evaluate costs and effects

Abstract: Pre-emptive isolation of suspected methicillin-resistant Staphylococcus aureus (MRSA) carriers is considered essential for controlling the spread of MRSA, but noncolonized patients will be isolated unnecessarily as a result of a delay in diagnosis of 3-5 days with conventional cultures. We determined costs per isolation day avoided, and incremental costs of rapid MRSA screening tests when added to conventional screening, but with decisions on isolation measures based on PCR results. A prospective multicentre s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 19 publications
1
105
0
2
Order By: Relevance
“…Similarly, in adult patients in a uk cf center, the prevalence increased from 1 % in 1985 to 6% in 2005 85 . In the Utrecht cf center, the prevalence of mrsa is very low (Table 1), which is similar to the low prevalence of mrsa in other patients in the Netherlands, where mrsa infection control policies consist of pre-emptive isolation of patients who are considered at high risk of mrsa carriage, until the absence of mrsa is proven 86 .…”
Section: Clinical Impactmentioning
confidence: 58%
“…Similarly, in adult patients in a uk cf center, the prevalence increased from 1 % in 1985 to 6% in 2005 85 . In the Utrecht cf center, the prevalence of mrsa is very low (Table 1), which is similar to the low prevalence of mrsa in other patients in the Netherlands, where mrsa infection control policies consist of pre-emptive isolation of patients who are considered at high risk of mrsa carriage, until the absence of mrsa is proven 86 .…”
Section: Clinical Impactmentioning
confidence: 58%
“…False-positive PCR results increase the number of patients in unnecessary isolation. Patient isolation is costly and cumbersome for hospital staff and has been associated in some settings with a reduced quality of patient care [30]. In our setting, the low MRSA Only for one of the two strains prevalence (3%) at hospital admission combined with a prevalence of about 3% of MLST CC1 isolates among MSSA carried by Belgian hospitalized patients led to a low PPV of the XP PCR assay.…”
Section: Discussionmentioning
confidence: 73%
“…This faster detection could, theoretically, shorten the delay in initiating contact isolation precautions for MRSA carriers and, therefore, lead to reduced cross-infection, length of hospital stay, and costs of hospital-acquired infections [28,29]. However, several studies have shown discordant results regarding the cost-effectiveness and effect on MRSA transmission of molecular screening compared with chromogenic cultures [30]. False-positive PCR results increase the number of patients in unnecessary isolation.…”
Section: Discussionmentioning
confidence: 97%
“…It has been calculated that isolation of a patient means an additional J26.34 each day on a regular ward in a non-outbreak situation (Wassenberg et al, 2010).…”
Section: Esbl Ligation-mediated Real-time Pcr Assaymentioning
confidence: 99%